JALAN MENIKUNG KARYA UMAR KAYAM: ANALISIS HEGEMONI GRAMSCI - , HALIMAH HASANAH H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this study are to give contribution thought about ideological contention, to determine theideologyandideologicalformations in UmarKayamâs Jalan Menikung, and also to understand consensusandUmarKayamâsideologies as the author of Jalan Menikung. This study uses Gramsci'stheory ofhegemonythat emphasizesthe importance ofspreadingideologytoachievehegemonyin society. Besides, this study uses descriptivemethodto analyze, combine with dialectial method. UmarKayamâs Jalan Menikung contains several ideologies, such as humanism, capitalism, materialism, traditionalism, theism, racialism, rationalism, nationalism, andliberalism. Ideologicalformationsandconsensusonhegemonyin UmarKayamâs Jalan Menikung show that UmarKayamâs Jalan Menikung has a minimumhegemony. Using ideologyof humanismandrationalismas anegotiator, subalterngroups(traditionalism, nationalism, andtheism) cohere together to show its reluctanceto ideology that dominate (capitalism, materialism, liberalism, andracism) Authorâs ideology was delivered viaLantipfigure. ThroughLantip,the ideology of traditionalism, theism,humanismandrationalism tries to be convey. InJalan Menikung, Umar Kayam show his thought that today ideologies must be filtered.